Low back pain among nursing assistants at Mansoura University hospitals: prevalence and risk - Faisal, Sarah; Abdel Rahman, Sherine; Abou-ElWafa, Hala; Al-Wehedy, Adel; Kamel, Emily (International Journal of Occupational Safety and Health, 2025)
Introduction: Low back pain (LBP) is one of the most debilitating and prevalent disorders. It is a leading contributor to disability worldwide. Lifting of heavy loads is a key duty of many healthcare workers, but among nursing assistants (NAs) patient handling is the most prevalent duty and has been reported as the main cause of LBP among them. Many studies reported higher prevalence of LBP for NAs compared with nurses and other occupational groups. This study aimed to determine the prevalence of LBP during the past 6 months and identify the potential associated risk factors among NAs. Methods: A cross-sectional study with analytic component was carried out upon all NAs working at three Mansoura university hospitals. An interviewer-administrated questionnaire was used to collect data regarding socio-demographics, work conditions, ergonomics, having LBP in the past 6 months, LBP characteristics and disability evaluation. Results: The prevalence of LBP in the past 6 months was 71.1% with 50.7% of them had clinically significant disability and 6.5% had severe disability. The prevalence of LBP with neurological symptoms was more than 50.0%, while 34.8% of them were taking regular medications for the pain. Female gender, obesity and most ergonomic risk factors were significantly higher among NAs with LBP than those without. Conclusion: It is evident from this study that LBP is prevalent among NAs. Personal and ergonomic risk factors contribute to its occurrence. Health and safety programs to build ergonomically safe working conditions, training of NAs and encouraging regular physical exercise are needed.